Patients with advanced and metastatic renal cell carcinoma treated with targeted therapy in the Czech Republic: twenty cancer centres, six agents, one database - Poprach, Alexandr; Bortlíček, Zbyněk; Büchler, Tomáš; Melichar, Bohuslav; Lakomý, Radek; Vyzula, Rostislav; Brabec, Petr; Svoboda, Marek; Dušek, Ladislav; Gregor, Jakub (Medical oncology (Northwood, London, England), 2012)
UNLABELLED: The incidence and mortality of renal cell carcinoma (RCC) in the Czech Republic are among the highest in the world. Several targeted agents have been recently approved for the treatment of advanced/metastatic RCC. OBJECTIVE: Presentation of a national clinical database for monitoring and assessment of patients with advanced/metastatic RCC treated with targeted therapy. The RenIS (RENal Information System, http://renis.registry.cz ) registry is a non-interventional post-registration database of epidemiological and clinical data of patients with RCC treated with targeted therapies in the Czech Republic. Twenty cancer centres eligible for targeted therapy administration participate in the project. As of November 2011, six agents were approved and reimbursed from public health insurance, including bevacizumab, everolimus, pazopanib, sorafenib, sunitinib, and temsirolimus. As of 10 October 2011, 1,541 patients with valid records were entered into the database. Comparison with population-based data from the Czech National Cancer Registry revealed that RCC patients treated with targeted therapy are significantly younger (median age at diagnosis 59 vs. 66 years). Most RenIS registry patients were treated with sorafenib and sunitinib, many patients sequentially with both agents. Over 10 % of patients were also treated with everolimus in the second or third line. Progression-free survival times achieved were comparable to phase III clinical trials. The RenIS registry has become an important tool and source of information for the management of cancer care and clinical practice, providing comprehensive data on monitoring and assessment of RCC targeted therapy on a national level.
Keywords: nádory ledvin; Molecular Targeted Therapy; protinádorové látky; karcinom z renálních buněk; Databases, Factual; Registries; Antineoplastic Agents; databáze faktografické; Carcinoma, Renal Cell; Humans; Česká republika; lidé; Czech Republic; Kidney Neoplasms; registrace; cílená molekulární terapie